1987
DOI: 10.1111/j.1469-1809.1987.tb01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and distribution of rare electrophoretic mobility variants in a population of human newborns in Ann Arbor, Michigan

Abstract: We have summarized the frequency and distribution of the rare variants encountered during the screening of 258,815 allele products, the products of 51 different loci, in 3242 predominantly Caucasian (88%) newborns. Seventy-nine different rare variants, representing 187 occurrences, were identified. Almost 60% (46 of 79) of the rare variants occurred as singletons while another 20% were seen in two unrelated individuals. No rare variants were detected at 18 loci while no variants, either rare or polymorphic, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Several studies demonstrated an allelic frequency from roughly 0.002 (Caucasian and Japanese population) to 0.02 (African American population) [5]–[9]. Indeed this number implies that 1 out of 2000 newborn individuals from the latter population would suffer from this tremendous disorder, but less than 100 individuals have been diagnosed with TPI deficiency worldwide [6]. A mutagenesis screen in mice identified four heterozygous TPI mutations that lead to a 50% reduction in catalytic TPI activity in several tissues examined [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated an allelic frequency from roughly 0.002 (Caucasian and Japanese population) to 0.02 (African American population) [5]–[9]. Indeed this number implies that 1 out of 2000 newborn individuals from the latter population would suffer from this tremendous disorder, but less than 100 individuals have been diagnosed with TPI deficiency worldwide [6]. A mutagenesis screen in mice identified four heterozygous TPI mutations that lead to a 50% reduction in catalytic TPI activity in several tissues examined [12].…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that mutations in the TPI gene resulting in a catalytic inactive TPI enzyme cause homozygote embryonic lethality in mice. The human population studies performed are indicating that this situation is reflected in humans as well [5], [6]. Consequently, the occurring mutations in TPI alleles of TPI deficiency patients cannot encode catalytically inactive TPI enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…It The reason for the apparent high frequency of vWD, as well as its extensive genetic heterogeneity, is unclear. The vWF gene does represent a large target for mutation, given its size, and such a factor has been postulated to contribute to the high frequency of mutation at other loci (28). Such …”
mentioning
confidence: 99%
“…This notwithstanding, we believe the series reported by Harris (8) to be relatively unbiased, and in our own studies (9,10), oriented toward the detection of mutation, the criterion for selecting a system for study was Marfan syndrome, and epidermalysis bullosa (discussion in refs. 32 and 33).…”
Section: Heterozygosity Indices Of the Proteins Detected In 2-d Page mentioning
confidence: 78%